Postnatal symptomatic Zika virus infections in children and adolescents: a systematic review - Ramond, Anna; Lobkowicz, Ludmila; Clemente, Nuria Sanchez; Vaughan, Aisling; Turchi, Marília Dalva; Wilder-Smith, Annelies; Brickley, Elizabeth B. (PLoS neglected tropical diseases, 2020)
Background Recent Zika virus (ZIKV) outbreaks in the Pacific and the Americas have highlighted clinically significant congenital neurological abnormalities resulting from ZIKV infection in pregnancy. However, little is known about ZIKV infections in children and adolescents, a group that is potentially vulnerable to ZIKV neurovirulence. Methods We conducted a systematic review on the clinical presentation and complications of children and adolescents aged 0 to 18 years with a robust diagnosis of ZIKV infection. We searched PubMed, Web of Science, LILACs, and EMBASE until 13 February 2020 and screened reference lists of eligible articles. We assessed the studies’ risk of bias using pre-specified criteria. Findings Our review collated the evidence from 2543 pediatric ZIKV cases representing 17 countries and territories, identified in 1 cohort study, 9 case series and 22 case reports. The most commonly observed signs and symptoms of ZIKV infection in children and adolescents were mild and included fever, rash, conjunctivitis and arthralgia. The frequency of neurological complications was reported only in the largest case series (identified in 1.0% of cases) and in an additional 14 children identified from hospital-based surveillance studies and case reports. ZIKV-related mortality was primarily accompanied by co-morbidity and was reported in one case series (<0.5% of cases) and three case reports. One death was attributed to complications of Guillain-Barré Syndrome secondary to ZIKV infection. Conclusions and relevance Based on the current evidence, the clinical presentation of ZIKV infection in children and adolescents appears to be primarily mild and similar to the presentation in adults, with rare instances of severe complications and/or mortality. However, reliable estimation of the risks of ZIKV complications in these age groups is limited by the scarcity and quality of published data. Additional prospective studies are needed to improve understanding of the relative frequency of the signs, symptoms, and complications associated with pediatric ZIKV infections and to investigate any potential effects of early life ZIKV exposure on neurodevelopment.
Gesehen am 10.11.2020